The Effectiveness of Group Guidance Using the Problem Solving Method to Improve Students' Academic Responsibility - Yoza Jumitra Yenti; Fitria Kasih; Besti Nora Dwi Putri (Journal of Practice Learning and Educational Development, 2026)
Academic responsibility is a crucial factor in supporting students’ learning success and academic achievement. Nevertheless, in educational practice, many students still demonstrate low levels of academic responsibility, which are reflected in poor time management, failure to complete individual assignments, lack of accuracy in answering questions, and inadequate preparation prior to learning activities. These conditions may negatively affect students’ learning outcomes if not addressed appropriately. Therefore, effective guidance interventions are needed to help students develop stronger academic responsibility. This study aimed to examine the effectiveness of group guidance using the problem solving method in improving students’ academic responsibility. The research employed a quantitative approach with a pre-experimental design, specifically a one group pretest–posttest model. The population consisted of 12 students, from which 10 students were selected as research samples using purposive sampling based on predetermined criteria. Data were collected through an academic responsibility questionnaire that measured students’ responsibility before and after the intervention. Data analysis techniques included percentage interval analysis to determine responsibility categories and a t-test to examine differences between pretest and posttest scores.The results revealed that prior to the intervention, students’ academic responsibility was generally categorized as low to moderate. After the implementation of group guidance using the problem solving method, students’ academic responsibility increased significantly to high and very high categories. Furthermore, the t-test results showed a significant difference between pretest and posttest scores (p < 0.05). These findings indicate that group guidance with the problem solving method is effective in enhancing students’ academic responsibility. Therefore, school counselors are encouraged to implement this method as an alternative strategy to foster students’ academic responsibility in schools